Keputusan Pembelian dari Aspek Desain Website, Kepercayaan, Keamanan dan Kemudahan - Dirwan Dirwan; Orfyanny S. Themba (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The purpose of this study was to analyze the effect of website design, trust, security and convenience on purchasing decisions on the Lazada application. The research was conducted using a quantitative approach with the type of conclusive research. The population of this study is infinite with the characteristics of the respondents, namely ITB Nobel Indonesia students who use the Lazada application, both male and female aged 19-23 years who have made purchases on the Lazada application. Questionnaires were distributed to 100 students. The data were analyzed and processed using multiple linear regression techniques through the IBM SPSS statistical analysis tool version 26. The results of the study found that website design, trust, security and convenience proved to have a positive and significant influence on purchasing decisions.